Penguatan Kader Masyarakat Dan Puskesmas Dalam Pengendalian Vektor Penyakit DBD Di RW 6 Kelurahan Gunung, Kecamatan Kebayoran Baru Jakarta Selatan Tahun 2023 - Agus Riyanto; Atang Saputra; Dini Syafitri (CV. Multi Kreasi Media, 2023)
Cases of dengue fever in the DKI Jakarta area still exist and the prevalence fluctuates so that education to the public is considered important to stop the transmission of dengue fever. One of the institutions responsible for environmental conditions is the Community Health Center, where Community Health Center cadres have the task of developing the community so that they can independently control the dengue vector. Gunung Village, which is in the Kebayoran Baru District, South Jakarta, which is part of the DKI Jakarta area, is an area where there are still cases of dengue fever, in 2019 there were 57 cases and in 2020 there were 13 cases, although there has been a decrease, it does not rule out the possibility that it will increase if there is a lack of awareness among community in keeping the environment clean and healthy. In the Gunung Village area, there are 7 RWs and 67 RTs. Strengthening training will be carried out by the Health Polytechnic of the Ministry of Health Jakarta II in collaboration with the Community Health Center for RW/RT cadres so that the community can be independent in carrying out control in order to reduce the morbidity rate of dengue fever by being equipped with knowledge in eliminating breeding and use places. ovitrap. This activity will be continuous and the results will be evaluated which can later be used as an example for other regions in controlling vector-borne diseases.